Organic Photonic Materials and Devices XXI 2019
DOI: 10.1117/12.2506261
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different polymers and printing technologies for realizing flexible optical waveguide Bragg grating strain sensor foils

Abstract: Waveguides with Bragg gratings realized on a flat polymer foil are promising candidates for advanced strain sensors since such a planar approach allows precise positioning of multiple sensors in various well-defined directions, in the same foil. As such, an optical version of an electrical strain gage can be realized. Herein, several parameters are discussed which define the behaviour of such sensor foils, in particular the grating design, including the wavelength of operation and mechanical and optical proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…To exclude this source of error and to obtain precise measurements, appropriate measures should be taken, for instance by rapidly varying the SOP and recording of averaged values. We focused on the quasi-static sensitivity with respect to temperature, strain, and humidity, and found our femtosecond laser-inscribed Bragg grating to perform similarly to those reported for other polymers and grating inscription techniques [6,10,32]. The sensitivity to strain is 0.26 pm/µε, sensitivity to temperature is −44 pm/K (at 43% relative humidity), and sensitivity to humidity is 19 pm/%, although these values are still influenced by the utilized substrate and cannot satisfy the requirement of general validity.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…To exclude this source of error and to obtain precise measurements, appropriate measures should be taken, for instance by rapidly varying the SOP and recording of averaged values. We focused on the quasi-static sensitivity with respect to temperature, strain, and humidity, and found our femtosecond laser-inscribed Bragg grating to perform similarly to those reported for other polymers and grating inscription techniques [6,10,32]. The sensitivity to strain is 0.26 pm/µε, sensitivity to temperature is −44 pm/K (at 43% relative humidity), and sensitivity to humidity is 19 pm/%, although these values are still influenced by the utilized substrate and cannot satisfy the requirement of general validity.…”
Section: Discussionmentioning
confidence: 52%
“…Missinne et al recently reported that their polymeric Bragg sensors have strain sensitivities in the range of 0.85-1.41 pm/µε. They further postulate that the photoelastic constant of optical polymers might be dependent on the Bragg wavelength, since the sensitivity did not scale solely with wavelength for their sensors with different grating pitches [10]. Nevertheless, simple strain variation of the Bragg sensor does not allow precise determination of the photoelastic constant, and further work has to be done.…”
Section: Strain Sensitivitymentioning
confidence: 99%
See 1 more Smart Citation
“…The change in RI of a material as a function of strain is given by the strain-optic coefficient, denoted as ρ [36]. Based on previously reported strain measurements with waveguide Bragg grating sensors made with the same materials [6,7,37], an estimation is made of the strain-optic coefficient for the used grating and waveguide materials, i.e., EpoCore: ρ = 0.31, and OrmoCore: ρ = 0.08. This extracted material data is used to simulate the effect of strain on the GMR grating signal.…”
Section: Polymer-based Guided Mode Resonance Strain Sensorsmentioning
confidence: 99%